Nutrients release from powder phonolite mediated by bioweathering actions - Laene de Fátima Tavares; André Mundstock Xavier de Carvalho; Luis Gustavo Brogliato Camargo; Samarina Gabriele de Fátima Pereira; Irene Maria Cardoso (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Silicate rock powders have been appointed as possible nutrient alternative sources which might enhance the agricultural sector sustainability. However, the application of those materials directly in soil presents as main limitations the low content and solubility of the mineral nutrient sources. In this perspective, the aim of the present study was to evaluate, in a bioweathering perspective, the conjunct application potential of phonolite with organic composts over the nutrients release in soil, as well as the production and nutrition of brachiaria grass (Urochloa decumbens). In addition, it was sought to assess the composting process effectiveness in improving the nutrient release from this rock. Method An experiment was conducted with five treatments (control; enriched compost with powder rock at 10%; mixed compost with powder rock at 10%; solely powder rock; solely compost) and four repetitions. Results The alternative sources positively influenced the productivity, as well as the K and Si contents at the aerial part of the brachiaria grass and the nutrient release in soil. However, the conjunct applications of powder phonolite with organic composts were the source which the best promoted the total nutrient biorelease to soil. Conclusion Nevertheless, there was no evidence that the composting process promotes the phonolite bioweathering. On the other hand, the conjunct application of powder phonolite with organic composts, either as an initial component to the composting pile or additive to the stabilized composts, is a strategy which enhances the nutrient biorelease of the mineral source.